Effectiveness of Marketing Activities in Engineering in Czech Republic - Milichovský, František (Business: Theory and Practice, 2015)
Purpose of the article is to present the selected data obtained from primary research, which concerns the marketing activities use in the Czech companies in view of their industry. Nowadays, high competitive environment influence permanent pressure on companies which are in turn force to monitor and adapt them in order to retain their expected market position. In article there were gained data by primary research, using a structure questionnaire survey and processing by statistical software IBM SPSS Statistics 22. The research sample consists 147 companies in 2013. All companies were operating in the Czech environment and they were chosen in random way from chosen CZ-NACE groups. The main scientific aim is to analyse the condition for realisation of marketing activities and determine whether there is a relationship between measurement of marketing effectiveness and industry field in the Czech business environment. Findings of the article point to differences in the use of individual marketing activities in view of engineering field. It was found that companies have to respect corporate goals to fill stakeholders᾿ requirements, with a small improving because of the engineering industry field. Through realisation marketing activities there are many ways how to impact target audience. Also, it was found there is only average dependency between tracking of marketing performance and engineering field. The result of the article is describing relevant approach to prove efficiency of realisation of marketing activities in relation with engineering companies. The companies know the importance of relationship with their customers. Marketing management and realisation of marketing activities has become realm where is possible to find opportunities to increase own competitiveness in view of the growing competitive environment.